Preparation of carbon nitride nanotubes with P-doping and their photocatalytic properties for hydrogen evolution. (May 2023) - Jang, Dawoon; Lee, Suyeon; Kwon, Nam Hee; Kim, Taehoon; Park, Sangjoon; Jang, Kyung Yeon; Yoon, Eojin; Choi, Seungjoo; Han, Juheon; Lee, Tae-Woo; Kim, Jeongho; Hwang, Seong-Ju; et al.
Abstract: Various carbon nitride (C3 N4 ) materials show great potential as an eco-friendly, visible-light-active photocatalyst for hydrogen evolution reaction (HER). In this work, a new route to produce one-dimensional (1D) P-doped carbon nitride nanotubes is developed via supramolecular self-assembly. The nanotubes are produced by thermal condensation of melamine and cyanuric acid. The addition of an ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate) improves the uniformity of the nanotubes. It is revealed that the C3 N4 nanotubes are formed by thermal condensation of rod-shaped intermediates. The nanotubes show an excellent photocatalytic HER activity under visible light irradiation and are a superior catalyst to 3D C3 N4 samples. From thorough structural and photophysical characterizations, it is found that the nanotubes contain larger surface areas, more amine bridges, better crystallinity, and more visible-light-absorption ability than control samples. These structural features are reasons for the enhanced photocatalytic performance. Graphical abstract: Image 1